Au/NiFe/M(Au, MoS2, graphene) trilayer magnetoplasmonics DNA-hybridized sensors with high record of sensitivity - Faridi, Ehsan; Moradi, Maryam; Ansari, Narges; Ghasemi, Amir Hossein Baradaran; Afshar, Amir; Mohseni, Seyed Majid (Journal of biomedical optics, 2017)
The demonstration of biosensors based on the surface plasmon effect holds promise for future high-sensitive electrodeless biodetection. The combination of magnetic effects with surface plasmon waves brings additional freedom to improve sensitivity and signal selectivity. Stacking biosensors with two-dimensional (2-D) materials, e.g., graphene (Gr) and MoS2, can influence plasmon waves and facilitate surface physiochemical properties as additional versatility aspects. We demonstrate magnetoplasmonic biosensors through the detuning of surface plasmon oscillation modes affected by magnetic effect via the presence of the NiFe (Py) layer and different light absorbers of Gr, MoS2, and Au ultrathin layers in three stacks of Au/Py/M(MoS2, Gr, Au) trilayers. We found minimum reflection, resonance angle shift, and transverse magneto-optical Kerr effect (TMOKE) responses of all sensors in the presence of the ss-DNA monolayer. Very few changes of ∼5×10−7 in the ss-DNA's refractive index result in valuable TMOKE response. We found that the presence of three-layer Gr and two-layer MoS2 on top of the Au/Py bilayer can dramatically increase the sensitivity by nine and four times, respectively, than the conventional Au/Co/Au trilayer. Our results show the highest reported DNA sensitivity based on the coupling of light with 2-D materials in magnetoplasmonic devices.